Analysis of android-based interactive multimedia needs analysis in learning biology in high school - Veni Wulandari; Aunurrahman Aunurrahman; Indri Astuti (JPBIO (Jurnal Pendidikan Biologi), 2023)
Education in the 21st century cannot be separated from technology-based learning. The existence of technology provides many conveniences in learning and has many choices depending on the needs of students, one of which is Android-based interactive multimedia. The purpose of this study was to analyze the needs of high school students before developing Android-based interactive multimedia in biology learning. This research is a qualitative descriptive study. The instrument used was a student response questionnaire. Questionnaires were given to 72 students at SMAN 1 Kayan Hilir. The data obtained were analyzed using a qualitative descriptive analysis technique. The results of this study indicate that 76% of students stated that mushroom material was considered the most difficult material, 93% of students want the development of new and fun learning multimedia and 87% of students want learning to use interactive multimedia based on Android. The conclusion from this study is that it is necessary to develop interactive learning multimedia based on android on mushrooms for class X SMA.